The Role of Viral Marketing in Social Media on Brand Recognition and Preference - Wilert Puriwat; Suchart Tripopsakul (Ital Publication, 2021)
Viral marketing is one of the most effective and imperative marketing strategies. The prominence of digital technology and social media has elevated the importance of viral marketing campaigns by increasing their cost efficiency and enabling them to reach targeted audiences rapidly. This study aimed to examine the influence of viral marketing strategies on brand recognition and brand preference by developing a framework for the effectiveness of viral marketing (7I’s) in social media contexts and testing the associations among the 7I’s, brand recognition and brand preference. A quantitative research method with a structured questionnaire as the research tool was employed to collect data from a total of 286 respondents in Thailand. Structural equation modelling (SEM) was utilized to test the proposed hypotheses. The results showed that effective viral marketing relates positively to brand recognition (b = 0.440) and preference (b = 0.298). The mediation analysis also revealed that brand recognition partially mediates the relationship between effective viral marketing and brand preference. In terms of the moderating effects, the results indicated a stronger influence for effective viral marketing on brand preference among younger respondents (b = 0.336) than among older respondents (b = 0.278). This research makes a significant contribution to the existing literature by validating a theory-driven framework based on the novel concept of the 7I’s and its potential effect on customers’ brand perceptions. Doi: 10.28991/esj-2021-01315 Full Text: PDF